2013
DOI: 10.2298/sarh1306337m
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum ferritin level in the prediction of delivery of low birth weight newborns for gestational age

Abstract: Based on the level of ferritin and other parameters in the period of 30-32 weeks of gestation, we can predict pregnant women in whom we can expect development of intrauterine growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the present study, the following cutoff points for maternal Hb were set in relation to the occurrence of LBW: 12.6 g/dL (1st trimester), 11.4 g/dL (2nd trimester), and 12.35 g/dL (3rd trimester). Milasinović et al (28) found that pregnant women with Hb values > 11.7 g/dL and ferritin concentrations above 13.6 ng/mL and hematocrit > 32.9% in the 30th to 32nd week of pregnancy were more likely to have restricted intrauterine growth and LBW infants, according to the analysis of the ROC curve. Their proposed cut-off point for Hb was similar to that found in the second trimester of pregnancy (11.4 stages, the production of red blood cells is compromised, and anemia can be detected by hemoglobin concentrations (≤ 11 g/dL in the first and third quarters and ≤ 10.5 g/dL in the second quarter) (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the following cutoff points for maternal Hb were set in relation to the occurrence of LBW: 12.6 g/dL (1st trimester), 11.4 g/dL (2nd trimester), and 12.35 g/dL (3rd trimester). Milasinović et al (28) found that pregnant women with Hb values > 11.7 g/dL and ferritin concentrations above 13.6 ng/mL and hematocrit > 32.9% in the 30th to 32nd week of pregnancy were more likely to have restricted intrauterine growth and LBW infants, according to the analysis of the ROC curve. Their proposed cut-off point for Hb was similar to that found in the second trimester of pregnancy (11.4 stages, the production of red blood cells is compromised, and anemia can be detected by hemoglobin concentrations (≤ 11 g/dL in the first and third quarters and ≤ 10.5 g/dL in the second quarter) (30).…”
Section: Discussionmentioning
confidence: 99%
“…The value of maternal serum ferritin in predicting asymmetric IUGR was previously investigated, for few times, on small numbers of cases, i.e. 7 cases in Ozgu-Erdinc et al [9] , 18 cases in Milasinovic et al [13] , 10 cases in Hubel et al [14] , 17 cases in Visnjevac et al [15] , and 31 cases in Bindal et al, [16] or with limitations in the research methodology such as measuring ferritin at a gestational age that was to early (20 weeks) or to late (36 weeks) [1,4] , or including cases with maternal iron deficiency anemia [15] .…”
Section: Discussionmentioning
confidence: 99%
“…[22] Hou et al, Milasinovic et al and Višnjevac et al identified the ferritin threshold to predict IUGR or SGA as >13.6 ng/ml. [4,13,15] Ozgu et al reported maternal serum ferritin levels >60 ng/ml to increase the risk for IUGR. [9] Bindal et al concluded that maternal serum ferritin >20 ng/ml predicted IUGR with an odds ratio of 6.6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations